Chemical Composition and Antifungal, Insecticidal and Repellent Activity of Essential Oils From Origanum compactum Benth. Used in the Mediterranean Diet - Aimad, Allali; Youness, El Abdali; Sanae, Rezouki; El Moussaoui, Abdelfattah; Bourhia, Mohammed; Salamatullah, Ahmad Mohammad; Alzahrani, Abdulhakeem; Alyahya, Heba Khalil; A. Albadr, Nawal; Nafidi, Hiba-Allah; Ouahmane, Lahcen; Mohamed, Fadli (Frontiers in Plant Science, 2022)
The essential oils (EO) of Origanum compactum Benth. (O. compactum) are well known for their biological and pharmacological activities. This study was aimed at assessing the chemical composition, antifungal and insecticidal activities of essential oil (EO) of O. compactum used in the Mediterranean diete. The phytochemical screening was conducted using gas chromatography-mass spectrometry (GC/MS). Antifungal activity was tested by disc diffusion method and minimal inhibitory concentration (MIC) against Candida albicans, Aspergillus flavus, Aspergillus niger, and Fusarium oxysporum. Repellent potential and toxicity of EO by contact and inhalation were performed against C. maculatus. The yield of essential oil obtained by hydrodistillation of O. compactum was 4.41 ± 0.35% majorly composed of Carvacrol (38%) and Thymol (31.46%). Regarding the antifungal activity, the results revealed a wide antifungal spectrum of the studied EO against the tested strains, which reached 100% growth inhibition especially against Aspergillus niger and Candida albicans even at the lowest MIC values (3.125 µg/mL). Concerning the insecticidal activity, the EO caused total mortality of Callosobruchus maculatus adults at a dose of 20 µL/L air with LC50 value of 5.3 µL/L air. A significant reduction in the number of eggs and emergence was proportionally recorded with increasing doses up to 100 % at 20 µL/L air. For the repellent activity, the studied EO showed a moderate repellent activity with an average percentage of 39.16%. The outcome of this work revealed that O. Compactum essential oils could be a sustainable and environmentally friendly alternative bioinsecticide and bio-fungicide to replace the chemically synthesized ones